The prevalence of manifest and latent celiac disease in type 1 diabetes mellitus - Serkan GÜVENÇ,; Sabahattin KAYMAKOĞLU,; Nuray GÜREL,; Kubilay KARŞIDAĞ,; Kadir DEMİR,; Dinç DİNÇER,; Çiğdem KEKİK,; Serpil SALMAN,; Temel YILMAZ,; Fatih BEŞIŞIK,; Yılmaz ÇAKALOĞLU, (Turkish Journal of Gastroenterology, 2019)
-